Occupational skin carcinogens - Kurtul, Seher; Güngördü, Nejdiye (The European Research Journal, 2024)
Occupational skin cancer may manifest when employees are under exposure to one specific carcinogenic substance or more in the workplace. Workplaces often have higher concentrations of carcinogens compared to any other setting. The most common causes of skin cancer in the workplace are ultraviolet radiation, ionizing radiation, polycyclic aromatic hydrocarbons, and arsenic. However, there is only a limited number of studies on skin cancer from occupational exposure. Skin cancers that are considered mainly work-related are non-melanoma skin cancers. Their most common variants are basal cell carcinomas, squamous cell carcinomas, and actinic keratosis. Two factors that reduced the risk of occupational carcinogen exposure are as follows: a better understanding of skin cancer risk factors involved in industrial processes and better control of the use of ionizing radiation. However, the exposure risk to ultraviolet radiation at dangerous levels remains. Worse still, this risk is often not considered. Yet, the prevention and risk reduction for occupational skin cancer requires the elimination of the contact of all carcinogens present in the workplace with the employees’ skin. Additionally, to encourage and facilitate the early recognition and management of premalignant and malignant skin lesions, training should be given to those working under higher skin cancer risk, and periodic examinations should be performed.